A new species of the genus Enoploderes Faldermann (Coleoptera, Cerambycidae, Lepturinae) - Lee, Seunghyun; Seung, Jinbae; Lee, Minhyeuk; Lee, Seunghwan (Zootaxa, 2023)
A new species of the genus Enoploderes Faldermann from South Korea, Enoploderes breviantennatus (이른봄꽃하늘소, i-reun-bom-kkot-ha-neul-so) is described. Full descriptions of both sexes with male genitalia and diagnosable characters comparing to its closest congener, Enoploderes bicolor Ohbayashi, 1941 are provided. Biological notes including photograph of eggs and larvae in nature are also provided.